KELAYAKAN USAHA KERAMBA JARING APUNG DENGAN SISTEM MONOKULTUR DAN POLIKULTUR DI TANJUNG MARTHAFONS KOTA AMBON - Leatemia, Tiffany Evangeline (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2019)
Fish culture in floating net cages can be done through monoculture and polyculture systems. Those systems have been carried out technically by farmers in Tanjung Marthaalfons Ambon Bay. The development of fish culture business does not only pay attention to technical issues, but also the level of fish mortality and operational costs. Thus, this business needs to be evaluated financially. Through survey, the data was collected from key informants, and analyzed in qualitative and quantitative descriptive method. The result shows that fish farming business with floating net cages in Tanjung Marthaalfons Ambon Bay in financially feasible to be developed. When the income is compared to regional minimum wage of Maluku, fish culture business with polyculture system is more profitable because the income is above the regional minimum wage value of Rp. 3,645,698 / month. The value of return on investment and revenue cost ratio of fish culture with polyculture systems is higher than monoculture systems, and its payback period is faster than monoculture systems.